Community Foundations : A Tool for Engaging Youth in Community Driven Development - Mesik, Juraj; Ringland, Vernon (World Bank, Washington, DC, 2012)
Community Driven Development (CDD) approaches present an effective means to involve young people in local development decision-making, giving them voice and influencing power, with benefits for themselves and their communities. This note highlights a range of key learning points emerging from years of international experience with youth banks, and youth advisory committees, an innovative tool for engaging youth in their communities. Community foundations hosting, youth advisory committees, or youth banks see youth in the community as a resource to be tapped into, not a problem to be solved. They see the best way for utilizing the energy and creativity of young people in giving them a large share of responsibility for the identification of youth needs and opportunities for youth engagement, selection of priority projects, grant making, implementation of projects, their monitoring as well as raising funds needed for the work.